Report of a series of healthy term newborns from convalescent mothers with COVID-19 - Perrone, Serafina; Deolmi, Michela; Giordano, Maurizio; D'Alvano, Tiziana; Gambini, Lucia; Corradi, Mara; Frusca, Tiziana; Ghi, Tullio; Esposito, Susanna (Acta Biomedica Atenei Parmensis, 2020)
Background: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly transmittable virus associated with a significantly increased risk of complications among the infected population. Few data are available for the outcome of pregnancy complicated by serious respiratory disease due to SARS-CoV-2 infection. Aim: We herein report a series of four neonates whose mothers had recovered from new coronavirus 2019 disease (COVID-19) diagnosed in the third trimester of pregnancy. Methods: pregnant women with documented COVID-19 infection during their pregnancy, who gave birth in Parma Hospital, University of Parma, Italy, in March and April 2020, during the peak of incidence of COVID-19 in Italy. Clinical records and laboratory tests were retrospectively reviewed. Results: All neonates were delivered at term in good conditions without congenital COVID-19 infection. Conclusions: Findings from our series of cases indicated that adverse effects on foetuses from pregnancies complicated by COVID-19 infection in late pregnancy are unlikely.